Social Entrepreneurs in Tourism Village: A Case in Batulayang Village, Cisarua, Bogor, West Java, Indonesia - Abdillah, Fitri; Syaiful Bahri, Asep (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2026)
Tourism villages, as one of the tourism industries, have an essential role in increasing the capacity and income of their people. In its development, a tourism village must have various strategies to realize a sustainable tourism village. One way to make this happen is by developing community-based tourism. The approach to implementing community-based tourism is to apply the concept of tourism social entrepreneur; this concept aims to create a community that can allow entrepreneurship to realize community-based and sustainable tourism. Batulayang Tourism Village, Bogor Regency, West Java Province, Indonesia is one of the tourist villages that relies on the community as the primary key in its development, so currently, Batulayang Tourism Village has become a sustainable tourism village. The purpose of this study is to describe the application of the concept of tourism social entrepreneur in Batulayang Tourism Village. The abbreviation carried out in this study is a qualitative case study approach by following a single holistic model that is commonly used to explain events as a whole. The results of this study show that Batulayang Tourism Village has utilized and optimized human capital, social capital, natural capital, and cultural capital to create various kinds of tourist attractions. With this capital, the people of Batulayang Tourism Village have created community-based enrichment of tourist attractions and realized sustainable tourism. Batulayang Tourism Village has been used as a reference or role model in developing community-based and sustainable tourism villages.